2013
DOI: 10.1587/elex.10.20130404
|View full text |Cite
|
Sign up to set email alerts
|

Hamming network circuits based on CMOS/memristor hybrid design

Abstract: Abstract:Memristor, as an innovative technology, has been proposed in the application of neural networks since its physical implementation was reported by HP lab. In this paper, we proposed a Hamming network circuits based on CMOS/memristor hybrid design which is compact in device size and circuit structure. Through HSPICE simulation, pattern recognition and classification functions of hamming network circuits are demonstrated using a 16 × 16 nanocrossbar memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…I o is the weighted summation of 8 I o,3 + 4 I o,2 + 2 I o,1 + I o,0 for recognizing ‘o’. The currents of I a , I i , I u , I e , and I o are compared with each other in the winner-take-all circuit [ 19 ] to decide which vowel is the best match with the voice input as shown in Figure 3 . Output a , Output i , Output u , Output e , and Output o are the output signals of the winner-take-all circuit.…”
Section: Methodsmentioning
confidence: 99%
“…I o is the weighted summation of 8 I o,3 + 4 I o,2 + 2 I o,1 + I o,0 for recognizing ‘o’. The currents of I a , I i , I u , I e , and I o are compared with each other in the winner-take-all circuit [ 19 ] to decide which vowel is the best match with the voice input as shown in Figure 3 . Output a , Output i , Output u , Output e , and Output o are the output signals of the winner-take-all circuit.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 2 a shows the complementary crossbar architecture which is composed of two memristor arrays of M + and M − [ 11 , 12 ]. The M − array in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…2 The crossbar array architectures of binary memristors for pattern recognition. a The complementary crossbar architecture [ 11 , 12 ]. b The twin crossbar architecture [ 10 ] …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using CMOS/memristor hybrid architecture and a two-part spike, Afifi et al demonstrated Spike-Timing-Dependent-Plasticity (STDP) learning implementation [5]. Zhu et al proposed an approach for implementing Hamming network based on hybrid CMOS/memristor circuit design [6], in which pattern recognition and classification were demonstrated.…”
Section: Introductionmentioning
confidence: 99%